2019
DOI: 10.1017/s1368980019001137
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D is associated with obesity and metabolic parameters in US children

Abstract: Objective:To explore the relationships of serum 25-hydroxyvitamin D (25(OH)D) with obesity and metabolic parameters in US children.Design:Cross-sectional analysis. We evaluated the associations between serum 25(OH)D and multiple measurements of adiposity, serum lipid concentrations, fasting glucose and insulin resistance in children aged 6–18 years with adjustments for multiple covariates.Setting:The National Health and Nutrition Examination Survey, 2001–2006.Participants:A nationally representative sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 55 publications
(58 reference statements)
5
31
0
Order By: Relevance
“…Here, we found vitamin D insufficiency was associated with abnormal TC only in girls. The gender difference may be due to reduced intake of vitamin D and the lack of outdoor activity 9. A Mendelian randomization study48 has provided the evidence that single nucleotide polymorphisms causing variations in 25(OH)D can lead to a genetically increased remnant lipoprotein-cholesterol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we found vitamin D insufficiency was associated with abnormal TC only in girls. The gender difference may be due to reduced intake of vitamin D and the lack of outdoor activity 9. A Mendelian randomization study48 has provided the evidence that single nucleotide polymorphisms causing variations in 25(OH)D can lead to a genetically increased remnant lipoprotein-cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular effects of vitamin D which are mediated by ubiquitous vitamin D receptor were found in the heart, kidneys, brain and muscles 4. It has been demonstrated that vitamin D deficiency may be associated with several cardiovascular-related conditions such as metabolic syndrome, diabetes mellitus, hypertension and coronary artery disease 5–9. In adults, longitudinal associations between serum 25-hydroxyvitamin D (25(OH)D) concentration and cardiometabolic risk factors were observed in a number of cohort studies 10–12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chronic inflammation that accompanied obesity develop to insulin resistance by the increased production of inflammatory cytokines from immune cell such as macrophages and adipocytes (Peterson et al, 2014). Similar to a study in China, it was stated that children with vitamin D deficiency had 4.15 times more at risk of developing insulin resistance than children without vitamin D deficiency (Fu et al, 2020). On the contrary, a study on 301 children aged 11-18 years in Turkey showed no significant relationship between insulin resistance and vitamin D status.…”
Section: Discussionmentioning
confidence: 77%
“…For more details about potential confounders in the NHANES, please refer to our previous studies [18,19]. In our analyses, we considered the following covariates: information on age (years), sex (male or female), race/ethnicity (non-Hispanic white, non-Hispanic black, Mexican American, or others), education levels (< high school, ≥high school), family poverty-income ratio (PIR), history of physiciandiagnosed diabetes (yes/no).…”
Section: Covariatesmentioning
confidence: 99%